Severe Pulmonary Mycobacterium abscessus Cases Due to Co-Infection with Other Microorganisms Well Treated by Clarithromycin and Sitafloxacin in Japan - Takano K; Shimada D; Kashiwagura S; Kamioka Y; Hariu M; Watanabe Y; Seki M (International Medical Case Reports Journal, 2021)
Kazuki Takano,1,2 Daishi Shimada,1 Shota Kashiwagura,1,3 Yasuhiro Kamioka,1,3 Maya Hariu,1,2 Yuji Watanabe,1,2 Masafumi Seki1 1Division of Infectious Diseases and Infection Control, Faculty of Medicine; 2Laboratory for Clinical Microbiology; 3Division of Pharmacy, Tohoku Medical and Pharmaceutical University Hospital, Sendai City, Miyagi, JapanCorrespondence: Masafumi SekiDivision of Infectious Diseases and Infection Control, Faculty of Medicine, Tohoku Medical and Pharmaceutical University, 1-15-1 Fukumuro, Miyagino-ku, Sendai City, Miyagi, 983-8612, JapanTel +81-22-259-1221Fax +81-22-290-8956Email m-seki@tohoku-mpu.ac.jpBackground: Mycobacterium abscessus frequently causes severe infections, yet its pathophysiological features and treatment regimens have not been established.Case Report: We present five cases of severe pneumonia due to Mycobacterium abscessus infection in Japan. All cases were diabetic patients, with possible acceleration to pneumonia due to co-infection with other microorganisms. However, following a short period of hospitalization and combination therapy with intravenous imipenem/cilastatin and amikacin, all the cases were successfully treated as outpatients with oral clarithromycin and sitafloxacin.Conclusion: M. abscessus infections can become severe in the presence of diabetes mellitus and co-infection with other chronic infectious organisms. Sitafloxacin might be a key drug in the treatment of M. abscessus infection in future.Keywords: non-tuberculosis mycobacterium, macrolides, clarithromycin, fluoroquinolone, sitafloxacin